Rancang Bangun Sistem Kontrol Kanopi Otomatis menggunakan Aplikasi Blynk Berbasis IoT - Yahya, Miftahul; Salahudin, Yanu; Erwanto, Danang (Fuse-teknik Elektro, 2025)
Frequent and unpredictable weather changes present a particular challenge for laundry businesses, especially when it comes to drying clothes during the rainy season. It is not uncommon for clothes that are almost dry to get wet again from sudden rain showers. These conditions are undoubtedly inconvenient and consume a significant amount of time and effort. To address this issue, this study designed an automatic canopy control system based on the Internet of Things (IoT). This system can quickly detect weather changes and provide users with convenience. The goal is to simplify the drying process and protect clothes from getting wet, which impacts service quality and business productivity. The system uses a Raindrop sensor to detect rainwater and an LDR sensor to measure light levels. A NodeMCU ESP8266 serves as the control centre and is connected to the internet. The microcontroller processes all sensor data and sends it to the Blynk app. This allows users to monitor drying conditions in real time via their smartphone and manually control the canopy if necessary. Test results show that the system responds well to weather changes and functions as intended. It is hoped that, with this system in place, the process of drying clothes will become more practical, efficient, and convenient so users no longer need to worry about unpredictable weather.